ENGLISH LANGUAGE PROFICIENCIES ARE ENTERED IN UZBEK LANGUAGE - Nomozova Marguba Allonovna (Galaxy International Interdisciplinary Research Journal, 2021)
In this article is given information about the historical division of modern Uzbek lexicon into two layers, own layer and mastered layer, classifying English learning on the basis of thematic groups and studying English words in socio-political, economic, cultural-educational and sports groups.